HEINER MÜLLER'S POSTEPIC DRAMA «MAUSER» - Vasylivska, N. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article provides the study of the features of the creative heritage of the poet and director, in 1995, the head of the Berliner Ensemble - Heiner Müller. The research was conducted in the context of the illumination of the steppe features of his drama. The basis of the experimental piece "Mauser" is taken, which is a continuation and at the same time the correction of the most famous Lehrstück Bertolt Brecht "Maβnahme". "Mauser" has become the latest "instructive model" in the creative heritage of the author, so it is assumed that this work is to some extent transmitted to Heiner Müller's post-hegemony. The work analyzes the plot, the structure of the play, its rigid, compressed speech style in the freely controlled rhythm of the iambic poem, the constant repetition of the metaphor and other poetic figures, thus demonstrating a new vision of the author of the principles of the epic theater Brecht. The peculiarity of the work of the chronotope is analyzed: the city of Vitebsk conditionally united in itself all the places where the spirit of the revolution was and is, and also the figure of the protagonist as a person who carried out "cleansing" in Vitebsk and did everything for the sake of the revolution and acts in the n ' Yes, as a symbolic figure, a certain social cluster. The views of theatrical critics on the work of Heiner Müller are described, the three periods of the author's creative path are briefly described (through the prism of the influence of the epic theater Bertolt Brecht). It is noted that the play "Mauser" refers to the second period of the work of Heiner Muller, but her parity is partially "overlapped" with its first phase. It is this parable character, conventionality of action, abstraction, projection to the past, present and future plays testify to the dramatic progression.